Micronutrients in health and disease - Prasad, Kedar N. (CRC Press/Taylor & Francis Group, 2011)
Assembling a plethora of rational and scientific evidence, this book makes the case that the use of not one but multiple micronutrients working together synergistically in combination with a low-fat, high-fiber diet can prove successful in the prevention and management of diseases ranging from cancer to posttraumatic stress disorder